Structural insights into heme binding to IL-36α proinflammatory cytokine - Wißbrock, Amelie; Goradia, Nishit B.; Kumar, Amit; Paul George, Ajay Abisheck; Kühl, Toni; Bellstedt, Peter; Ramachandran, Ramadurai; Hoffmann, Patrick; Galler, Kerstin; Popp, Jürgen; Neugebauer, Ute; Hampel, Kornelia; et al. (Scientific Reports, 2019)
Cytokines of the interleukin (IL)-1 family regulate immune and inflammatory responses. The recently discovered IL-36 family members are involved in psoriasis, rheumatoid arthritis, and pulmonary diseases. Here, we show that IL-36α interacts with heme thereby contributing to its regulation. Based on in-depth spectroscopic analyses, we describe two heme-binding sites in IL-36α that associate with heme in a pentacoordinated fashion. Solution NMR analysis reveals structural features of IL-36α and its complex with heme. Structural investigation of a truncated IL-36α supports the notion that the N-terminus is necessary for association with its cognate receptor. Consistent with our structural studies, IL-36-mediated signal transduction was negatively regulated by heme in synovial fibroblast-like synoviocytes from rheumatoid arthritis patients. Taken together, our results provide a structural framework for heme-binding proteins and add IL-1 cytokines to the group of potentially heme-regulated proteins.
CRIS-Team Scopus Importer:2019-11-26